Fluctuation of spittlebug population in brachiaria and in elephant grass - Auad, Alexander Machado; Carvalho, Caio Antunes de; Silva, Daniela Maria da; Deresz, Fermino (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the fluctuation of spittlebug population in Brachiaria brizantha, Brachiaria decumbens and Pennisetum purpureum. The evaluations were conducted in field conditions, between September 2005 and March 2007. Spittlebug nymphs and adults were counted on B. brizantha cultivars Marandu, Xaraés and Arapoti, subjected to alternating grazing; on B. decumbens in a silvipastoral system and on 78 genotypes of P. purpureum. The Deois schach population density was greater on the Arapoti cultivar than on the Xaraés and Marandu cultivars. On B. decumbens, the number of spittlebugs was four times greater than on B. brizantha. No significant differences were observed in the number of spittlebugs infesting the different genotypes of P. purpureum.
Keywords: Brachiaria brizantha; Brachiaria decumbens; Deois schach; Pennisetum purpureum; Cercopidae; pest resistance